Immune Regulation of Intrahepatic Regulatory T Cells in Fibrotic Livers of Mice - Zhang, Xiaohui (Med Sci Monit, 2017)
BACKGROUND: Liver fibrosis is the result of chronic inflammation and repair, and many immune cells contribute to the process. Regulatory T cells (Tregs) mediate immune tolerance and are highly expressed in liver fibrosis. However, few reports have studied the specific effects of Tregs on regulating immune cells in liver fibrosis. The present study aimed to investigate the regulation of Tregs on intrahepatic immune cells in liver fibrosis by depleting Tregs in mice. MATERIAL/METHODS: Liver fibrosis was induced by carbon tetrachloride, and an anti-CD25 mAb (PC61) was used to deplete Tregs. Liver fibrosis and injury were reflected by immunofluorescence staining and alanine aminotransferase level. The expressions of immune cell Tregs and cytokines were detected by flow cytometry and/or real-time PCR. Interferon-γ (IFN-γ) concentration was measured by ELISA. RESULTS: Tregs were rich in fibrotic livers; after Tregs depletion, the intrahepatic CD4(+) T cell and Kupffer cells (KC) populations did not change compared with liver fibrosis, but CD8(+) T cells were slightly elevated. However, natural killer (NK) cells and IFN-γ levels were significantly decreased in fibrosis and increased after Tregs depletion. Interesting, we found Tregs promoted KC M1/M2 balance to M2, because inducible nitric oxide synthase (M1) was increased but arginase-1 (M2) was reduced after depleting Tregs. Furthermore, in isolated KCs from livers, IL-12 (M1) was increased, but TGF-β (M2) was reduced after depleting Tregs, compared with fibrotic livers. CONCLUSIONS: Tregs are involved in the immune regulation of liver fibrosis, primarily by suppressing NK cells and M1 KCs, and mildly suppressing CD8(+) T cells.